Livelihood Strategies and Income Level of People of Modi Watershed, Nepal - Rijal, Shiba Prasad (Himalayan Review, 2009)
The analysis of livelihood strategies and income level of the people of Modi Khola watershed is the main purpose of this study. The study result is based on sampling of 360 households from 12 selected communities of the Modi Khola watershed having 676.8 km2 area and 75,000 populations. The people of Modi Khola area adopt diverse livelihood strategies such as farming including livestock raising, service in government and non-governmental agencies, business, tourism, industrial activities, migration, wage labor, fi shing, forest product collection and others. Livelihood strategies vary by household and localities as a result of spatial variation in terms of availability of assets, people's capabilities for exploiting the assets and environment. Household members adopt one or more activities to meet their household needs. Spatial variation is found in income distribution too. Households adopting diverse strategies have higher income and more secure livelihoods as compared to the households adopting single or lesser number of activities. Key words: Livelihoods, strategies, options, capabilities, combination, sustainable, environment, diversity. The Himalayan Review Vo. XXXVII, 2006 Page: 19-37